If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x(x + -1) + 13 = 7 Reorder the terms: 6x(-1 + x) + 13 = 7 (-1 * 6x + x * 6x) + 13 = 7 (-6x + 6x2) + 13 = 7 Reorder the terms: 13 + -6x + 6x2 = 7 Solving 13 + -6x + 6x2 = 7 Solving for variable 'x'. Reorder the terms: 13 + -7 + -6x + 6x2 = 7 + -7 Combine like terms: 13 + -7 = 6 6 + -6x + 6x2 = 7 + -7 Combine like terms: 7 + -7 = 0 6 + -6x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(1 + -1x + x2) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(1 + -1x + x2)' equal to zero and attempt to solve: Simplifying 1 + -1x + x2 = 0 Solving 1 + -1x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-1' to each side of the equation. 1 + -1x + -1 + x2 = 0 + -1 Reorder the terms: 1 + -1 + -1x + x2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x + x2 = 0 + -1 -1x + x2 = 0 + -1 Combine like terms: 0 + -1 = -1 -1x + x2 = -1 The x term is -1x. Take half its coefficient (-0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = -1 + 0.25 Reorder the terms: 0.25 + -1x + x2 = -1 + 0.25 Combine like terms: -1 + 0.25 = -0.75 0.25 + -1x + x2 = -0.75 Factor a perfect square on the left side: (x + -0.5)(x + -0.5) = -0.75 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 1/14(0-8)-9 | | g(b+6)=3x-1 | | 3b^3+9b^2= | | 8(w-6)-(7-4w)=11w | | 8x=20/75 | | 3x/5=-4/9 | | (X^2+1)(x^4-2x^3-5x^2-6x)=0 | | -6w+12=42 | | -9=1-5w | | 28x^2-61+21=0 | | -29=4w-9 | | -11-3y=7 | | 4(2y+1)=34 | | 4x+-3(x+5)=10 | | 2x(-3x+5)=6 | | 3r^3+24r^2=60r | | z=4-1/9x^2-1/16y^2 | | 2(c-6)+7c=5-3(-2) | | y=3600+.8(Y-200)+600+1200 | | f(x)=3sqrt(X+3-3) | | F(2065)=895+30g | | 3-6(-5y+4)=3(-y+1)-6 | | log^6x=3 | | 3(x-2)+7=3x+27 | | -19(2a-3b+8c)= | | 13x-2(4x-5)=66-3x | | 5z^2-37zy+42y^2=0 | | 72+24w=288 | | 3(4x-3)= | | 2ln(x)=4 | | 24+16p=4p | | 24x-32=24x+36 |